Community gardens as a response to the contradictions of sustainable urban policy: Insights from the Swiss cities of Zurich and Lausanne - Jahrl, Ingrid; Ejderyan, Olivier; Salomon Cavin, Joëlle (Frontiers in Sustainable Food Systems, 2022)
In this paper we explore how policy discourses on urban sustainability impact the governing of urban food gardening in favoring community gardens. Our main hypothesis is that community gardens better accommodate the tensions created by the discourses of the compact and green city compared to other types of food gardening, especially allotment gardens. In the context of the Swiss cities of Lausanne and Zurich, analysis of policy documents confirms this hypothesis by identifying four frames that orient policies toward favoring community gardening: (i) Adapting green space planning to densification favors community gardening with their modest, flexible and multifunctional design, (ii) Revaluating the role of urban food gardening in urban sustainability represents community gardening as a new multifunctional benchmark, (iii) Reorganizing urban food gardening fosters diversity in gardening opportunities which in turn supports a variety of forms of community gardening, (iv) Justifying urban food gardening through public values and needs supports community gardening with their cost-efficient green space management, lower land management and more active citizen participation. In this vein, urban policymakers continually turn to community gardens as a strategic urban planning tool that gives urban green space greater legitimacy in the wake of the densifying city. Overall, urban food gardens continue to be negotiated between space-related marginalization and socio-political significance serving different needs to urban citizens. This results in the need of a more sophisticated planning approach considering different types of urban gardens related to their location in the built city, associated functions, and user groups.